Cultural Hegemony of Islamic Student Marriage Arrangement in Novel Jadilah Purnamaku, Ning, Wigati, Hati Suhita By Khilma Anis - Maria Ulfa, Titin; Nuryatin, Agus (Universitas Negeri Semarang, 2021)
Literature work is human mind production by projecting real events. Literature work has many life values for readers. The novel is a part of literary work that tells the daily problems completely that are acted out by the characters. This research aims to review the marriage arrangement hegemony realization in Khilma Anis works and review the hegemonic acceptance realization of marriage arrangement in Khilma Anis works. This research is a literature-sociology approached research. The technique of analyzing the data was done by heuristically reading and hermeneutics interpreting the events, such as the words, sentences, and dialogs in the novel. The results showed that Jadilah Purnamaku, Ning had two characters that hegemonically succeed to matchmake their children. It was persuasive hegemony and destructively done with intellectual and moral leadership. The hegemonic acceptance realization occurred totally and degenerately. Wigati's novel was found to have two hegemonic characters that were successfully hegemonic. The hegemony was found to be moralized and intellectual leaderships. The acceptance realizations of both characters occurred totally. In Hati Suhita's novel, there are two hegemony and hegemonic characters. Both hegemony characters had intellectual leadership and the hegemonic acceptance realizations occurred degenerately. Then, these changed into a total acceptance from other characters. Theoretically, this research could deepen the previous studies and allow new theory findings. Thus, it could contribute to sociology field literature knowledge. Practically, it could improve the literacy of readers and improve the loving feeling of literature work as a life inspiration via the written stories. It could also inspire the accurate hegemony ways so other people will not feel to be insisted but to accept it voluntarily